Language Attitude of the Fourth Semester English Education Department Students Toward Their Speaking Skill Implemented in the Classroom - Intan Niawati; Bibit Suhatmady; Satyawati Surya (E3L: Journal of English Teaching, Linguistic, and Literature, 2020)
Language attitude is considered as the key factor that influence students’ motivation to learn and determine the results of studying a language. Therefore, the objective of this study is to find out the fourth semester students’ language attitude toward their speaking skill implemented in the classroom and the factors affecting their attitudes. The research methodology utilized a qualitative case study design. The participants of this study were six students of the fourth semester of English Education Department at Mulawarman University which were selected by using purposive sampling. The data of this research were collected through interview and were analyzed by using Thematic Analysis adopted from Braun and Clarke (2006). The findings discovered that three students have positive attitudes and the others have negative attitudes. Ideally, student with positive attitude will have good score in speaking. However, the researcher found that P4 has negative attitude even though she has middle score in speaking. This case is caused by internal and external factors that make P4 has negative attitude. Moreover, findings also showed that students’ positive attitude were mainly influenced by parents’ roles, teacher’s attitudes, inter-ethnic contact and some psychological factors such as self-confidence and high motivation. In addition, students’ negative attitudes were influenced by lack of desire to speak English and teacher high expectation. Further research may be recommended to find out different factors that might affect student’s attitude with different methodology such as conduct some observations in the classroom to see the implementation of students speaking skill which can reflect their attitude and enrich the data findings. Language attitude knowledge could help the students to motivate them in maintaining their positive attitude. Besides, parents and English teacher could support and encourage the students to increase their positive attitude in learning a language